Impact of public debt on economic growth, health expenditure and poverty in sub-Saharan Africa countries - Sani, Abdullahi (2018)
This thesis presents the empirical studies on three important issues in sub-Saharan African countries. Firstly, while other regions with good institutional quality have benefitted considerably from borrowing, sub-Saharan Africa (SSA) continue to accumulate public debt with a long history of dismal economic performance. The first part of this study examines the relationship between public debt and economic growth highlighting the role of institutional quality in SSA. Using the Generalized Method of Moments (GMM) approach, a sample of 46 sub-Saharan African countries were examined over the period 2000–2014. The empirical result confirmed that institutional quality has both a direct and an indirect impact on economic growth and also institutional quality has a statistically significant impact on the debt-growth relationship in sub-Saharan Africa. This confirms the hypothesis that the impact of public debt on economic growth is a function of institutional quality. Therefore, comprehensive improvement of the institutional quality is necessary not only in minimizing the negative impact of public debt but also in delivering the unwavering benefits of government borrowing. Secondly, for the countries in SSA characterized by unfavourable balance-of-payment and a whopping budgetary gap to bridge, continuous accumulation of debt can never be free of cost. These countries have to earmark a sizable proportion of their limited resources to debt servicing, which is expected to reduce their overall government spending and health expenditure in particular. The second part of this study examines the impact of public debt burden on health expenditure in SSA highlighting the role of institutional quality. Using the Generalized Method of Moments (GMM) approach, a sample of 43 SSA countries were examined over the period 2000 –2014. The empirical result confirms that the public debt burden has a negative impact on public health expenditure in sub-Saharan Africa. However, with the inclusion of the interaction term of institutional quality and public debt burden the negative impact turns out to be positive. This suggests that the impact of public debt burden on health expenditure in sub-Saharan Africa is a function of institutional quality. Therefore, to improve the level of public health expenditure in SSA governments need to take a determined stand to mobilize the domestic resources, minimize public debt accumulation and improve institutional quality. Thirdly, the high level of indebtedness has been frequently mentioned as an impediment to the successful alleviation of poverty in developing countries. The third objective examines the relationship between public indebtedness and the incidence of poverty in sub-Saharan Africa. Using the Generalized Method of Moment approach, a sample of 42 SSA countries was examined over the period 2000-2014. The empirical results confirmed that public indebtedness has a statistically significant positive impact on poverty in sub-Saharan Africa. This suggests that public indebtedness is one of the leading cause of the lingering mysteries of the dogged poverty in SSA. Therefore, to alleviate poverty, proper utilization of the domestic resources and reduction in public debt accumulation is necessary.